Do firms defer or accelerate green investment under carbon price uncertainty? - Chengxing Xie; Liang Wu; Zhijie Tong (Borsa Istanbul Review)
This study examines how carbon price uncertainty (CPU) in China's regional carbon markets shapes firms' green investment (GI) decisions, addressing a critical gap in empirical and regional research. Using granular data from eight Chinese regional carbon markets and listed firms' green expenditure records, we demonstrate that rising CPU accelerates GI commitments. It indicates that, contrary to the traditional ‘wait-and-see’ approach posited by real options theory, firms actively hedge against market-induced climate risks rather than deferring investments. This effect is amplified for firms facing lower financing constraints, operating in low-carbon industries, or located in regions with advanced green financial infrastructure. Robustness checks and instrumental variable analysis validate these results. Our analysis further establishes that internal active carbon management and external green investor participation constitute dual transmission channels through which CPU stimulates firms' commitment to financing green initiatives.